A metakaolin-based inorganic texture coating and its preparation method and application
By adding textured aggregate particles to metakaolin-based inorganic coatings, the problems of easy cracking and lack of texture are solved, and the effects of strong adhesion, excellent decorativeness and cost reduction are achieved, and the construction market is adapted to the diversified needs.
Patent Information
- Application Number
- CN202310194204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-03
AI Technical Summary
The existing metakaolin-based inorganic architectural coatings lack texture and are prone to cracking, which cannot meet the diversified needs of the construction market.
By adding textured aggregate particles, combining metakaolin, water glass, quartz powder, activated magnesium oxide, wollastonite powder, expanded perlite powder and redispersible latex powder, a metakaolin base with strong adhesion and excellent decorative properties is prepared. Inorganic texture coatings improve the crack resistance and wear resistance of the coating.
It provides three-dimensional shapes with different styles, enhances the crack resistance and wear resistance of the paint, while reducing costs and adapting to the diversified needs of the construction market.
Smart Images

Figure BDA0004106584510000071 
Figure BDA0004106584510000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a metakaolin-based inorganic texture coating and a preparation method and application thereof. Background Art
[0002] Kaolin-based inorganic building coatings are healthy, green, safe and environmentally friendly. They also have the characteristics of strong adhesion, high hardness, washability and long life. In addition, they have the advantages of wide source of raw materials, low cost, easy transportation and storage.
[0003] At present, metakaolin-based inorganic architectural coatings are mainly composed of fine powder as the main raw material. After being painted and solidified, they become smooth surfaces of various colors, lacking texture, and therefore cannot meet the diversified requirements of the construction market, limiting its widespread use. In addition, metakaolin-based inorganic coatings have the defect of being easy to crack. Summary of the invention
[0004] The present invention provides a metakaolin-based inorganic textured coating, a preparation method and application thereof. The coating provided by the present invention has strong adhesion to a substrate, excellent comprehensive performance and excellent decorative properties.
[0005] The invention provides a metakaolin-based inorganic textured coating, comprising a metakaolin-based inorganic coating base material and textured aggregate particles; the metakaolin-based inorganic coating base material comprises the following components in parts by weight: 21-23 parts of metakaolin, 17-19 parts of water glass, 44-46 parts of quartz powder, 1-3 parts of active magnesium oxide, 5-7 parts of wollastonite powder, 2-4 parts of expanded perlite powder, 1-3 parts of redispersible latex powder, and 0-2 parts of additives; the textured aggregate particles are heavy aggregates or lightweight aggregates; the heavy aggregate is 4-100 parts, and the lightweight aggregate is 2-20 parts.
[0006] Preferably, the heavy aggregate includes river sand, quartz sand, natural colored sand, and limestone; the light aggregate includes rubber particles and expanded vermiculite.
[0007] Preferably, the auxiliary agent is 0-0.4 parts of water retaining agent, 0-0.2 parts of defoaming agent, 0-0.4 parts of leveling agent, 0-0.8 parts of dispersant, 0-0.1 parts of anti-sagging agent, and 0-0.1 parts of wetting agent.
[0008] Preferably, the redispersible latex powder is a copolymer of vinyl acetate-ethylene, with a fineness of ≥100 mesh and a water content of ≤1.5%.
[0009] Preferably, the metakaolin has a fineness of ≥500 mesh, a water content of ≤1.5%, and a whiteness of ≥80%.
[0010] Preferably, the modulus of the water glass is 2, the fineness is ≥300 mesh, and the water content is ≤1.5%.
[0011] Preferably, the expanded perlite powder has: fineness ≥300 mesh, water content ≤1.5%, and whiteness ≥90%; the quartz powder has a fineness ≥600 mesh, a water content ≤1.5%, and a whiteness ≥80%; the activated magnesium oxide has a fineness ≥300 mesh, a water content ≤1.5%, and a whiteness ≥90%; the wollastonite powder has a fineness ≥300 mesh, a water content ≤1.5%, and a whiteness ≥92%.
[0012] Preferably, the particle size of the textured aggregate particles is 50 to 80 meshes.
[0013] The present invention provides a method for preparing the metakaolin-based inorganic texture coating described in the above scheme, comprising the following steps:
[0014] (1) stirring metakaolin, water glass, quartz powder, activated magnesium oxide, wollastonite powder, expanded perlite powder, redispersible latex powder and additives to obtain a base material;
[0015] (2) Mixing the base material of step (1) with texture aggregate particles to obtain a metakaolin-based inorganic texture coating.
[0016] The present invention provides the use of any one of the above-mentioned metakaolin-based inorganic texture paints as a building paint. When using the metakaolin-based inorganic texture paint, the metakaolin-based inorganic texture paint is mixed with water to obtain a slurry, and the slurry has a water-cement ratio of 0.3.
[0017] Compared with the prior art, the advantages and positive effects of the present invention are:
[0018] Adding textured aggregate particles to kaolin-based inorganic architectural coatings has the following advantages: (1) it can provide three-dimensional shapes of different styles, and can also obtain different tones through its own color or by matching other colors; (2) it can improve the coating's anti-cracking ability and make up for the easy cracking defect of kaolin-based inorganic architectural coatings; (3) it can improve the coating's wear resistance; (4) it can reduce the coating cost and facilitate market promotion. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The invention provides a metakaolin-based inorganic textured coating, comprising a metakaolin-based inorganic coating base material and textured aggregate particles; the metakaolin-based inorganic coating base material comprises the following components in parts by weight: 21-23 parts of metakaolin, 17-19 parts of water glass, 44-46 parts of quartz powder, 1-3 parts of active magnesium oxide, 5-7 parts of wollastonite powder, 2-4 parts of expanded perlite powder, 1-3 parts of redispersible latex powder, and 0-2 parts of additives; the textured aggregate particles are heavy aggregates or lightweight aggregates; the heavy aggregate is 4-100 parts, and the lightweight aggregate is 2-20 parts.
[0021] The metakaolin-based inorganic textured coating provided by the present invention comprises a metakaolin-based inorganic coating base material. In the present invention, the metakaolin-based inorganic coating base material comprises 21-23 parts by weight of metakaolin. In the present invention, the fineness of the metakaolin is preferably ≥500 mesh, more preferably 500-1000 mesh; the water content is preferably ≤1.5%, and the whiteness is preferably ≥80%.
[0022] In the present invention, the metakaolin-based inorganic coating base material comprises 17-19 parts by weight of water glass. In the present invention, the modulus of the water glass is preferably 2; the fineness is preferably ≥300 mesh, more preferably 300-1000 mesh; and the water content is preferably ≤1.5%.
[0023] In the present invention, the metakaolin-based inorganic coating base material comprises 44-46 parts by weight of quartz powder. In the present invention, the fineness of the quartz powder is preferably ≥600 mesh, more preferably 600-1000 mesh; the water content is preferably ≤1.5%, and the whiteness is preferably ≥80.
[0024] In the present invention, the metakaolin-based inorganic coating base material includes 1-3 parts by weight of active magnesium oxide. In the present invention, the fineness of the active magnesium oxide is preferably ≥300 mesh, more preferably 300-1000 mesh; the water content is preferably ≤1.5%, and the whiteness is preferably ≥90%.
[0025] In the present invention, the metakaolin-based inorganic coating base material includes 5-7 parts by weight of wollastonite powder. In the present invention, the fineness of the wollastonite powder is preferably ≥300 mesh, more preferably 300-1000 mesh; the water content is preferably ≤1.5%, and the whiteness is preferably ≥92%.
[0026] In the present invention, the metakaolin-based inorganic coating base material includes 2-4 parts by weight of expanded perlite powder. In the present invention, the expanded perlite powder preferably has a fineness of ≥300 mesh, more preferably 300-1000 mesh, a water content of ≤1.5%, and a whiteness of ≥90.
[0027] In the present invention, the metakaolin-based inorganic coating base material includes 1-3 parts by weight of redispersible latex powder. In the present invention, the redispersible latex powder is a copolymer of vinyl acetate-ethylene, with a fineness of ≥100 mesh, more preferably 100-1000 mesh; and a water content of ≤1.5%.
[0028] In the present invention, the metakaolin-based inorganic coating base includes 0-2 parts by weight of an auxiliary agent. In the present invention, the auxiliary agent is preferably 0-0.4 parts of a water retaining agent, 0-0.2 parts of a defoaming agent, 0-0.4 parts of a leveling agent, 0-0.8 parts of a dispersant, 0-0.1 parts of an anti-sagging agent, and 0-0.1 parts of a wetting agent. The present invention has no particular limitation on the specific source of the auxiliary agent, and conventional commercial products in the field can be used.
[0029] The metakaolin-based inorganic texture coating provided by the present invention includes texture aggregate particles, which are classified as heavy aggregate or lightweight aggregate according to the bulk density, the heavy aggregate is 4 to 100 parts by weight, and the lightweight aggregate is 2 to 20 parts by weight. In the present invention, the heavy aggregate preferably includes river sand, quartz sand, natural colored sand, and limestone; the lightweight aggregate preferably includes rubber particles and expanded vermiculite. In the present invention, the particle size of the texture aggregate particles is preferably 50 to 80 meshes.
[0030] The metakaolin-based inorganic textured coating provided by the present invention has a large amount of textured aggregate added therein. The textured aggregate can provide different three-dimensional shapes for the surface of architectural coatings to decorate buildings; the textured aggregate can reduce the shrinkage of geopolymer materials, improve the volume stability of the coating, and reduce the cracking of the metakaolin-based coating caused by volume shrinkage to a certain extent; the textured aggregate can also increase the thickness and flexibility of the metakaolin-based coating, and when cracks appear in the coating, the cracks are easily covered, so the crack resistance and wear resistance of the coating can be improved; adding a large amount of cheap aggregate particles to the coating can also reduce the cost of the coating; although the coating thickness is relatively thin, the appropriate particle size and addition amount can improve the surface texture of the coating, and the selected textured aggregate can adapt to the alkaline environment, so it will not affect the stability of the coating, and will not have a negative impact on other properties of the coating.
[0031] The present invention provides a method for preparing the metakaolin-based inorganic texture coating described in the above scheme, comprising the following steps:
[0032] (1) stirring metakaolin, water glass, quartz powder, activated magnesium oxide, wollastonite powder, expanded perlite powder, redispersible latex powder and additives to obtain a base material;
[0033] (2) Mixing the base material of step (1) with texture aggregate particles to obtain a metakaolin-based inorganic texture coating.
[0034] The present invention stirs metakaolin, water glass, quartz powder, active magnesium oxide, wollastonite powder, expanded perlite powder, redispersible latex powder and an auxiliary agent to obtain a base material. In the present invention, the stirring speed is preferably 400-500 r / min.
[0035] After obtaining the base material, the present invention mixes the base material with texture aggregate particles to obtain a metakaolin-based inorganic texture coating. In the present invention, the mixing method is preferably stirring, and the stirring speed is preferably 50 to 200 r / min.
[0036] The present invention first mixes the metakaolin-based inorganic coating base material, and then mixes the texture aggregate particles with the base material. The materials are mixed twice, which can not only fully mix the materials, but also does not destroy the aggregate particles and does not affect the texture performance of the coating.
[0037] The present invention provides the use of any one of the above-mentioned metakaolin-based inorganic texture paints as a building paint. When using the metakaolin-based inorganic texture paint, the metakaolin-based inorganic texture paint is mixed with water to obtain a slurry, and the slurry has a water-cement ratio of 0.3.
[0038] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0039] The parameters of each component in each embodiment are as follows:
[0040] The fineness of metakaolin is 500 mesh, the water content is ≤1.5wt%, and the whiteness is ≥80%; the modulus of water glass is 2, the fineness is 300 mesh, and the water content is ≤1.5%; the fineness of the expanded perlite powder is 300 mesh, the water content is ≤1.5%, and the whiteness is ≥90%; the fineness of the quartz powder is 600 mesh, the water content is ≤1.5%, and the whiteness is ≥80%; the fineness of the activated magnesium oxide is 300 mesh, the water content is ≤1.5%, and the whiteness is ≥90%; the fineness of the wollastonite powder is 300 mesh, the water content is ≤1.5%, and the whiteness is ≥92%.
[0041] Example 1
[0042] 22 parts of metakaolin, 18 parts of water glass, 45 parts of quartz powder, 2 parts of active magnesium oxide, 6 parts of wollastonite powder, 3 parts of expanded perlite powder, 2 parts of redispersible latex powder, 2 parts of additives (0.4 parts of water retaining agent, 0.2 parts of defoaming agent, 0.4 parts of leveling agent, 0.8 parts of dispersant, 0.1 parts of anti-sagging agent, 0.1 parts of wetting agent), 60 parts of quartz sand particles (quartz sand product parameters: particle size 50-80 mesh, water content ≤1.5%, whiteness ≥80%)
[0043] Mixing metakaolin, water glass, active magnesium oxide, wollastonite powder, redispersible latex powder, expanded perlite and additives in a shear mixer at a speed of 400 r / min to obtain a mixed base;
[0044] Add quartz sand particles to the above base material and stir in a mixer at a speed of 50r / min to mix thoroughly and evenly, seal and pack in moisture-proof bags, and store in a dry place at room temperature. When using, add water to the prepared powder raw material to make a slurry with a water-cement ratio of 0.3 to make a textured paint, which can be used for brushing, roller coating, and spraying until the desired three-dimensional shape is achieved.
[0045] Example 2
[0046] The difference from Example 1 is that the quartz sand is replaced by 60 parts of natural colored sand (particle size 50-80 mesh, water content ≤1.5%, yellow).
[0047] Example 3
[0048] The difference from Example 1 is that the quartz sand is replaced by 60 parts of limestone (particle size 50-80 mesh, water content ≤1.5%, whiteness ≥80%).
[0049] Example 4
[0050] The difference from Example 1 is that the quartz sand is replaced by 10 parts of rubber particles with a particle size of 50-80 mesh.
[0051] Example 5
[0052] The difference from Example 1 is that the amount of quartz sand particles is 40 parts.
[0053] Example 6
[0054] The difference from Example 1 is that the quartz sand is replaced by 40 parts of natural colored sand.
[0055] Example 7
[0056] The difference from Example 1 is that the quartz sand is replaced by 40 parts of river sand.
[0057] Example 8
[0058] The difference from Example 1 is that the quartz sand is replaced by 40 parts of limestone.
[0059] Example 9
[0060] The difference from Example 1 is that the quartz sand is replaced by 4 parts of rubber particles.
[0061] Example 10
[0062] The difference from Example 1 is that the quartz sand is replaced by 4 parts of expanded vermiculite particles.
[0063] Comparative Example 1
[0064] The difference from Example 1 is that quartz sand particles are 1 part.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that 150 parts of quartz sand particles are used.
[0067] Comparative Example 3
[0068] The difference from Example 1 is that the quartz sand is replaced by 40 parts of rubber particles.
[0069] Performance Testing
[0070] The relevant properties of the metakaolin-based coatings prepared in the examples and comparative examples were tested, and the specific test items included: 1. coating texture; 2. water resistance; 3. alkali resistance; 4. freeze-thaw resistance; 5. tensile bond strength; 6. tensile bond strength after freeze-thaw resistance. The specific test results are shown in Table 1.
[0071] Table 1 Test results
[0072]
[0073]
[0074] As can be seen from Table 1, the texture coatings prepared in Examples 1-10 passed the water resistance, alkali resistance, and freeze-thaw resistance tests, and the coatings had a good appearance, and the coatings did not bulge, crack, or fall off; at the same time, the tensile bonding strength of Examples 1-10 and the tensile bonding strength after five freeze-thaw cycles were both higher than the standard requirements. The texture coatings prepared in Comparative Examples 1-3 did not meet the standard requirements in all their properties.
[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A metakaolin-based inorganic texture coating, It is characterized in that The invention is composed of a metakaolin-based inorganic coating base material and texture aggregate particles; the metakaolin-based inorganic coating base material is composed of the following components in parts by weight: 21-23 parts of metakaolin, 17-19 parts of water glass, 44-46 parts of quartz powder, 1-3 parts of active magnesium oxide, 5-7 parts of wollastonite powder, 2-4 parts of expanded perlite powder, 1-3 parts of redispersible latex powder, and 0-2 parts of additives; the texture aggregate particles are heavy bone Aggregate or lightweight aggregate; the heavy aggregate is 4-100 parts, the lightweight aggregate is 2-20 parts; the heavy aggregate includes river sand, quartz sand, natural colored sand, limestone; the lightweight aggregate includes rubber particles, expanded vermiculite; the additives include 0-0.4 parts of water retaining agent, 0-0.2 parts of defoaming agent, 0-0.4 parts of leveling agent, 0-0.8 parts of dispersant, 0-0.1 parts of anti-sagging agent, and 0-0.1 parts of wetting agent; The metakaolin has a fineness of ≥500 mesh, a water content of ≤1.5%, and a whiteness of ≥80%; The water glass has a modulus of 2, a fineness of ≥300 mesh, and a water content of ≤1.5%; The expanded pearlite powder: fineness ≥ 300 mesh, water content ≤ 1.5%, whiteness ≥ 90%; the quartz powder: fineness ≥ 600 mesh, water content ≤ 1.5%, whiteness ≥ 80%; the activated magnesium oxide: fineness ≥ 300 mesh, water content ≤ 1.5%, whiteness ≥ 90%; the wollastonite powder: fineness ≥ 300 mesh, water content ≤ 1.5%, whiteness ≥ 92%; The particle size of the textured aggregate particles is 50 to 80 meshes.
2. The metakaolin-based inorganic texture coating according to claim 1, It is characterized in that The redispersible latex powder is a copolymer of vinyl acetate and ethylene, with a fineness of ≥100 meshes and a water content of ≤1.5%.
3. The method for preparing the metakaolin-based inorganic texture coating according to any one of claims 1 to 2, It is characterized in that The steps include: (1) stirring metakaolin, water glass, quartz powder, activated magnesium oxide, wollastonite powder, expanded perlite powder, redispersible latex powder and additives to obtain a base material; (2) Mixing the base material of step (1) with texture aggregate particles to obtain a metakaolin-based inorganic texture coating.
4. Use of the metakaolin-based inorganic texture coating according to any one of claims 1 to 2 as a building coating, It is characterized in that When in use, the metakaolin-based paint is mixed with water to obtain a slurry, and the slurry has a water-cement ratio of 0.3.
Citation Information
Patent Citations
Coating material with metakaolin as film forming substance and preparation thereof
CN101302363A
Geopolymer dry-powder paint as well as preparation and use method thereof
CN103555011A
Waterproof and anti-alkali decorating mortar and preparation method thereof
CN107010880A
Anti-crack geopolymer-based inorganic powder coating as well as preparation method and application thereof
CN114196242A
Inorganic polymer mortar and preparation method thereof
CN114230249A
